2022
DOI: 10.3390/ijms231911738
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Cellulose Acetate Membranes for Separation of Fermentation Broths by the Reverse Osmosis: A Feasibility Study

Abstract: Recently, there has been a special research focus on the bioconversion of glycerol to 1,3-propanediol (1,3-PD) due to its significance in the chemical industry. However, the treatment and separation of fermentation broths is a great challenge. Currently, the reverse osmosis (RO) process is a reliable state-of-the-art technique for separation of biological solutions. This study (as the first to do so) investigated the feasibility of separation of 1,3-PD broths with the use of cellulose acetate (CA) membrane by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…This membrane is made of regenerated cellulose acetate in polypropylene, and it has little tolerance to aqueous solutions. In the bibliography, it is shown that cellulose acetates are susceptible to being hydrolyzed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This membrane is made of regenerated cellulose acetate in polypropylene, and it has little tolerance to aqueous solutions. In the bibliography, it is shown that cellulose acetates are susceptible to being hydrolyzed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CA-RO membranes have been used for desalination [46,48,99,100], to remove ammonium from aqueous solutions [101], a trace of organic compounds and micropollutants are rejected from water more effectively by the CA-RO membranes [102], and fermentation broth separation [103].…”
Section: Cellulose Acetate Ro Membranementioning
confidence: 99%
“…The investigations have been focused on the separation of 1,3-PD fermentation broths obtained via glycerol fermentation with the use of Citrobacter freundii bacteria. The detailed information on the fermentation process conditions have been presented in several previous articles [39,45,48,49]. After the fermentation, the broths contained bacteria; 1,3-PD; glycerol; mono-carboxylic acids (lactic, acetic and formic acid) and dicarboxylic acid (succinic acid); and ethanol, as well as residual bacterial growth medium.…”
Section: Fermentation Brothsmentioning
confidence: 99%